Factors contribute towards smoking habit among FSPPP male students: A case study at UiTM Bandaraya Melaka / Norhaiza Ahmad and Siti Nurliyana Zahari - Ahmad, Norhaiza; Zahari, Siti Nurliyana (Faculty of Administrative Science and Policy Studies, 2013)
This chapter focuses on the background of the study which is factors contribute towards smoking habit among FSPPP male students at UiTM Melaka City Campus. The first section discusses on the background of the study, the next section explains the problem statement and the third section states the research objectives. In addition, the fourth section states the scope of research and the last section explains the significant of study.